2012
DOI: 10.1111/j.1471-6712.2012.01087.x
|View full text |Cite
|
Sign up to set email alerts
|

Community nurses' experiences of ethical problems in end‐of‐life care in the patient's own home

Abstract: The nurses exhibited commitment and a desire to do good when caring for patients in the end-of-life phase, even if they sometimes experienced feelings of lack of control. This implies that, when confronted with care-related issues, they have the power to both act and react. This study aimed to increase understanding of ethical problems that arise in end-of-life care in the patient's own home and revealed the need to take the patients', relatives' and nurses' perspectives on health and suffering into considerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 21 publications
2
44
1
Order By: Relevance
“…“The patient's home is the place where her/his identity is protected from the outside of the world and where her/his identity is confirmed”, (p. 832)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…“The patient's home is the place where her/his identity is protected from the outside of the world and where her/his identity is confirmed”, (p. 832)…”
Section: Resultsmentioning
confidence: 99%
“…“The home can be seen as an inner room (private space) where the person is at home with her/himself”, (p. 832)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nurses may experience unsanitary conditions, demanding care activities, the need to perform heavy lifts and time-consuming travel between patients (Leiss, 2012;Markkanen et al, 2007). Further, nurses have reported that working in private homes can include having insufficient medical and collegial support, contributing to feelings of discomfort, insecurity and loneliness during work (Carlson, Ramgard, Bolmsjo, & Bengtsson, 2014;Karlsson, Karlsson, da Silva, Berggren, & Soderlund, 2013;Tunnah & Johnstone 2012). However, positive aspects are more frequently described and it has been suggested that the home environment promotes opportunities to create caring relationships which can, however, be emotionally challenging for the nurse when the patient dies (Markkanen et al, 2007).…”
Section: Backg Rou N Dmentioning
confidence: 99%